Evaluation of Brucellosis Vaccines: A Comprehensive Review - Heidary, Mohsen; Dashtbin, Shirin; Ghanavati, Roya; Mahdizade Ari, Marzie; Bostanghadiri, Narjess; Darbandi, Atieh; Navidifar, Tahereh; Talebi, Malihe (Frontiers in Veterinary Science, 2022)
Brucellosis is a bacterial zoonosis caused by Brucella spp. which can lead to heavy economic losses and severe human diseases. Thus, controlling brucellosis is very important. Due to humans easily gaining brucellosis from animals, animal brucellosis control programs can help the eradication of human brucellosis. There are two popular vaccines against animal brucellosis. Live attenuated Brucella abortus strain 19 (S19 vaccine) is the first effective and most extensively used vaccine for the prevention of brucellosis in cattle. Live attenuated Brucella melitensis strain Rev.1 (Rev.1 vaccine) is the most effective vaccine against caprine and ovine brucellosis. Although these two vaccines provide good immunity for animals against brucellosis, the expense of persistent serological responses is one of the main problems of both vaccines. The advantages and limitations of Brucella vaccines, especially new vaccine candidates, have been less studied. In addition, there is an urgent need for new strategies to control and eradicate this disease. Therefore, this narrative review aims to present an updated overview of the available different types of brucellosis vaccines.